Strengthening Character Education Through the Application of Religious Culture to Support the Pancasila Student Strengthening Project (P5) in Junior High Schools - Rasidah, Rasidah; Iqbal, Muhammad; Najmuddin, Najmuddin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to describe the forms of character education strengthening programs and the inhibiting and supporting factors for the implementation of religious culture to support the project of strengthening the Pancasila student profile (P5) at SMP Negeri 2 Takengon. This qualitative research was conducted at SMP Negeri 2 Takengon. This research is qualitative, holistic, and descriptive in terms of words and language in a special, natural context, and it utilizes various natural methods. This research will be conducted at SMP Negeri 2 Takengon. The data collection techniques are observation, in-depth interviews, and documentation review. Data analysis techniques are data reduction, data modeling, and conclusion verification. The results of this study are the school's efforts to strengthen character education through the application of religious culture to support the P5 project at SMP Negeri 2 Takengon Forms of strengthening character education through the application of religious culture to support the project to strengthen the profile of Pancasila students (P5) at SMP Negeri 2 Takengon including morning greeting activities, tahsin and tahfidz activities, women's activities/rohis, speech activities, literacy, Yasinan and Friday alms and activities to commemorate Islamic holidays. These activities have been proven to strengthen students' character and can support the project of strengthening the profile of Pancasila students. The supporting factors so that these activities can be carried out properly and continuously to strengthen the character of students are the principal's commitment and support from the teacher council, adequate facilities and infrastructure, and good management. The students' enthusiasm in participating in various religious and cultural activities. The factors that hinder the strengthening of students' character through religious culture to support the project of strengthening the profile of Pancasila students are the family or community environment, peers, the presence of activity coaches, and the lack of mastery of reading the Quran.